Implantation of a scleral fixated (Carlevale) EDOF IOL in aphakia - Petros Petrou; Spyridon Doumazos; Stylianos A. Kandarakis; Aikaterini Barlampa; Stergios Ntikos; Eirini Okoutsidou; Georgia Karageorgiou; Ilias Georgalas (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To present a case of lens dislocation in which an Extended Depth of Focus (EDOF) scleral fixated (Carlevale) intraocular lens (IOL) was inserted after performing pars plana vitrectomy (PPV) and lens fragmentation. Case report: A 68-year-old woman presented to our department with loss of vision in her right eye after a blunt trauma in the right eye. After clinical examination the patient was aphakic with a dropped nucleus in the vitreous cavity. Surgical plan involved PPV with lens fragmentation and insertion of an IOL. Due to patient circumstances, she requested spectacle independence as far as possible. In order to support her needs a custom made Carlevale EDOF scleral fixated IOL (FIL SSF EVOLVE) was successfully implanted in her right eye with excellent post operative results. Excellent distant visual acuity as well as good intermediate and near vision was achieved 3 months post-operative in our patient. Conclusion: According to previous reports as well as from our own previous experience, achieving efficient scleral fixation using the Carlevale FIL SSF IOL seems like a promising option in cases of aphakia or zonular dehiscence. EDOF lens technology is widely used in routine cataract surgery for demanding patients who require a wider range of vision without glasses. Combining these two technologies lead to a lens design (Carlevale FIL SSF EVOLVE) that we used in this case and enabled us to help our patient and improve her quality of life.